(untitled) (American Journal of Technology and Applied Sciences, 2023)
In the article, molecular physics related to the significant progress achieved at the atomic-molecular level, as well as the wide use of new physics, a deeper penetration into the essence of microprocesses in the construction processes and the consideration of corpuscular models depending on the atomic-molecular structure, molecules, atoms, ions that form wet materials, it is recommended to take into account the interaction forces between bodies.